1963
DOI: 10.1103/physrev.130.1505
|View full text |Cite
|
Sign up to set email alerts
|

Bremsstrahlung from Proton Bombardment of Nuclei

Abstract: I I I 4y-tea. * U m , M k lt aa4 U r tk it h i-alagla >r«tW M lM » M l l i l t M , l«4 M i l t i P H tn |MM4 M M M M M l pktMMMlnlMl M tlM C M elM U tM tU tM. TIm »»m-i l o l c i l t t M l m t la 41m m n 4 La DO) , Kurattaofla a-a d) ■ y t o t w iM lM * la ta ra o tia a k |

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1964
1964
1978
1978

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…At incident proton energies below the threshold for TT° production, the y radiation produced could be ascribed to NNy, and the predicted ratio 6 (Tnpy/crppy^ 10 suggested that nearly all of it was due to npy inside the nucleus. Such experiments were performed by Wilson, 13 Cohen et a/., 14 and Edgington and Rose. 15 However, the extraction of quantitative information about free npy from such measurements is both difficult and dubious, as shown by Beckham, 16 who contributed the most applicable theoretical treatment of bremsstrahlung from proton-nucleus collisions and applied it to the measurements of Cohen et al u He found that the exclusion principle caused a strong reduction of the radiation production, especially for photons of high energy, and that the choice of the momentum distribution for the target nucleons critically affected the calculated cross sections.…”
mentioning
confidence: 99%
“…At incident proton energies below the threshold for TT° production, the y radiation produced could be ascribed to NNy, and the predicted ratio 6 (Tnpy/crppy^ 10 suggested that nearly all of it was due to npy inside the nucleus. Such experiments were performed by Wilson, 13 Cohen et a/., 14 and Edgington and Rose. 15 However, the extraction of quantitative information about free npy from such measurements is both difficult and dubious, as shown by Beckham, 16 who contributed the most applicable theoretical treatment of bremsstrahlung from proton-nucleus collisions and applied it to the measurements of Cohen et al u He found that the exclusion principle caused a strong reduction of the radiation production, especially for photons of high energy, and that the choice of the momentum distribution for the target nucleons critically affected the calculated cross sections.…”
mentioning
confidence: 99%